Some health hazard metals in commercially important coastal molluscan species in Bangladesh (Bangladesh Journal of Zoology, 2016)
The present study was conducted to measure the heavy metals (Pb, Cd, Hg) concentrations in the muscles of four edible mollusk species (Perna viridis, Crassostrea crassostrea, Sepia officinalis and Loligo edulis) for two seasons. The heavy metal concentrations were analyzed by Atomic Absorption Spectrophotometer (AAS). The wet weight concentration of heavy metals varied for Pb: 0.03 - 0.05 1mg/kg, Cd 0.03 - 0.04 mg/kg and Hg 0.01 - 0.023 mg/kg. The trend of metals in mollusk muscles were found as Pb > Cd > Hg. There was no significant variation of Cd and Hg concentrations in mollusk species that were analyzed, but Pb varied (F = 22.297; p = 0.00), in terms of both seasons and species. Principal Component Analysis and correlation matrix showed significant anthropogenic intrusions of Pb, Cd and Hg in mollusks. There was significant positive correlation between Cd vs Pb (1.00) and Hg vs Cd (0.447) indicates their common origin especially from industries and municipal wastes. The determined concentrations of all metals in the present study were lower than the limits permitted by World Health Organization (WHO) and European Union (EU) guidelines.Bangladesh J. Zool. 44(1): 123-131, 2016